Double-blind review favours increased representation of female authors. - Budden, A; Tregenza, T; Aarssen, L; Koricheva, J; Leimu, R; Lortie, C (2008)
Double-blind peer review, in which neither author nor reviewer identity are revealed, is rarely practised in ecology or evolution journals. However, in 2001, double-blind review was introduced by the journal Behavioral Ecology. Following this policy change, there was a significant increase in female first-authored papers, a pattern not observed in a very similar journal that provides reviewers with author information. No negative effects could be identified, suggesting that double-blind review should be considered by other journals.